Short-term global health research projects by US medical students: ethical challenges for partnerships. - Provenzano, Audrey M; Graber, Lauren K; Elansary, Mei; Khoshnood, Kaveh; Rastegar, Asghar; Barry, Michele (The American journal of tropical medicine and hygiene, 2010)
Recent interest in global health among medical students has grown drastically, and many students now spend time abroad conducting short-term research projects in low-resource settings. These short-term stints in developing countries present important ethical challenges to US-based students and their medical schools as well as the institutions that host such students abroad. This paper outlines some of these ethical issues and puts forth recommendations for ethically mindful short-term student research.
Keywords: Biomedical Research; Developing Countries; Education, Medical, Undergraduate; Ethics, Medical; Ethics, Research; Healthcare Disparities; Humans; Informed Consent; International Cooperation; Program Development; Schools, Medical; Students, Medical; Time Factors; United States; World Health